Determining patterns in the stresseddeformed state of the railroad track subgrade reinforced with tubular drains - Luchko, Josyp; Kovalchuk, Vitalii; Kravets, Ivan; Gajda, Oleksiy; Onyshchenko, Arthur (Eastern-European Journal of Enterprise Technologies, 2020)
The technical condition of the railroad track subgrade has been analyzed, as well as the issues related to ensuring its strength and stability when exposed to floodwaters and when the track’s sections are overmoistened during operation. As a result, it has been established that it is necessary to develop methods aimed at improving the subgrade’s carrying capacity. The georadar research has explored the problematic areas of the railroad track subgrade, based on which the distribution of subgrade heterogeneity in the vertical plane, as well as the boundaries of its location, were established. Therefore, georadar research makes it possible to detect hidden defective sites in the subgrade without disrupting its strength characteristics. A technique has been proposed to improve the carrying capacity of the failed subgrade of a railroad track using the combined arrangement of drainage pipes in the vertical and horizontal directions in the railroad embankment. The special feature of this technique is the possibility to drain water at the different levels of surface water, which provides for an increase in the carrying capacity of the failed subgrade. The strained-deformed state of the subgrade reinforced with tubular drainage has been investigated. The result has proven the effectiveness of the use of tubular drainages to improve the carrying capacity of the railroad track overmoistened subgrade exposed to constant and temporary loads. This study findings have established that the deformity of the subgrade increases when using tubular drainage, though this occurs only in the initial period of its arrangement, in further operation, when it removes water from the subgrade body, the carrying capacity of the subgrade, on the contrary, will improve due to the enhanced physical and mechanical properties of soils